Pergeseran Arah Strategis Arab Saudi: Studi Anomali Normalisasi Hubungan dengan Iran melalui Mediasi Tiongkok Tahun 2023 - Sukmatika, Anak Agung Yumas (Neolectura, 2026)
This study examines the normalization of relations between Saudi Arabia and Iran through China’s mediation in March 2023, employing constructivism and role theory as analytical frameworks. Using Norman Fairclough’s critical discourse analysis on official documents, diplomatic statements, and media reports, the study reveals a shift in Saudi Arabia’s identity from a confrontational actor to a regional balancer. The choice of China as mediator reflects Riyadh’s strategy of diversifying partnerships and repositioning itself within a multipolar order. The normalization thus signifies not merely pragmatic policy, but a broader transformation of Saudi Arabia’s identity and role in Middle Eastern diplomacy.